DEVELOPING PROBLEM-BASED LEARNING MODULE TO IMPROVE THE FOURTH-GRADE STUDENTS’ LEARNING ACHIEVEMENT MOTIVATION - Nela Rofisian; Isna Rahmawati (The University of Kuningan, 2020)
The purposes of the study were to: 1) Develop a problem based learning module for the fourth-grade students, and 2) Discover the feasibility of the learning module. This study was conducted by using Research and Development (RD) as proposed by Borg and Gall (1983). In the field test stage, 52 fourth-grade students were involved as participants in an experimental design. The participants were divided into two group, while one group conducted learning by implementing the PBL Module, the other group conducted learning on regular basis with textbook from the government. The qualitative data were analyzed using qualitative method, and the quantitative data were analyzed by using Wilcoxon test. The results of this study reveal that: 1) The PBL Module was developed in accordance with PBL syntax; 2) The results of the development PBL modules was feasible to be applied. The feasibility of PBL Modules based on the expert validation, validation of practitioners, and small-scale trial respondents obtains the